IOC World Conference on Prevention of Injury & Illness in Sport 2021 (British Journal of Sports Medicine, 2021)
The IOC World Conference on Prevention of Injury & Illness in Sport (6th edition) is the premier international conference for those interested in clinical aspects of sports and exercise medicine. The diverse faculty represent the pre-eminent international authorities in injury and illness prevention. This triennial conference is a unique opportunity for the global sport and exercise medicine community to meet face to face in the ideal environment that Monaco provides.